Auditory Intellectually Repetition (AIR) Learning Model Assisted by Microsoft Sway: Influence on Students' Learning Outcomes in Physics Science Lessons - Suryani, Yani; Yuberti, Yuberti; Sari, Dian Novita (Jurnal Pembelajaran Fisika, 2024)
The increasing need for effective learning models in education has led researchers to explore various instructional methods and tools. Among these, the Auditory Intellectually Repetition (AIR) learning model has shown promise in enhancing student engagement and comprehension. The purpose of this study was to determine the impact of the AIR learning model supported by Microsoft Sway on student performance in a physics science classroom. The study population consisted of 92 eighth-grade students of MTs Muhammadiyah Sukarame, Bandar Lampung, Indonesia divided into experimental and control groups using purposive sampling techniques. Data were collected through a 10-question written test and analyzed using an independent samples t-test. Results indicated that the AIR learning model significantly improved student learning outcomes, with the experimental group outperforming the control group (p < 0.05). The AIR model's integration with Microsoft Sway facilitated interactive and engaging learning, enhancing student understanding and retention. The study underscores the potential of combining innovative learning models with digital tools to address common educational challenges, such as low student engagement and poor comprehension. These findings align with the broader educational objective of leveraging technology to foster higher-quality learning experiences. By incorporating listening, reasoning, and repetition, the AIR model promotes active student participation and intellectual development, making learning more effective and enjoyable. This research highlights the importance of adopting such integrative approaches to improve educational outcomes and suggests future studies could explore combining different digital tools with varied learning models to maximize student potential.Keywords: Auditory intellectually repetition (AIR), learning model, learning outcomes, Microsoft SwayDOI: http://dx.doi.org/10.23960/jpf.v12.n1.202402